AVALIAÇÃO PÓS-OCUPAÇÃO DE HABITAÇÕES FAIXA 1 DO PROGRAMA MINHA CASA MINHA VIDA EM UBERLÂNDIA-MG: ESTUDO DE CASO RESIDENCIAL JARDIM MAANAIM - Ciloni, Arquimedes; Alves, Camila; Salomão, Maria Cláudia (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The post occupancy evaluation (POE) as a methodology for the evaluation of built environments has been highlighted and shown to be important for the improvement of the productive cycle of the constructions, the results produced have contributed in a significant way in the identification of failures and designation of qualities in the projects. The main objective of this study is to evaluate the satisfaction of the residents of Residencial Jardim Maanaim, located in the city of Uberlândia-MG. The neighborhood is a development of the band 1 of the Minha Casa Minha Vida Program, composed of 206 housing units. The research was based on the application of POE in social housing through technical observations and the application of structured interview questionnaires, in which 68 families were interviewed. The results were presented through graphs, and it was possible to observe that occupants had difficulties in adapting to the standard project therefore modifying its housing unit.